Protein kinase C iota regulates pancreatic acinar-to-ductal metaplasia. - Michele L Scotti; Kristin E Smith; Amanda M Butler; Shelly R Calcagno; Howard C Crawford; Michael Leitges; Alan P Fields; Nicole R Murray (PLoS ONE, 2012)
Pancreatic acinar-to-ductal metaplasia (ADM) is associated with an increased risk of pancreatic cancer and is considered a precursor of pancreatic ductal adenocarcinoma. Transgenic expression of transforming growth factor alpha (TGF-α) or K-ras(G12D) in mouse pancreatic epithelium induces ADM in vivo. Protein kinase C iota (PKCι) is highly expressed in human pancreatic cancer and is required for the transformed growth and tumorigenesis of pancreatic cancer cells. In this study, PKCι expression was assessed in a mouse model of K-ras(G12D)-induced pancreatic ADM and pancreatic cancer. The ability of K-ras(G12D) to induce pancreatic ADM in explant culture, and the requirement for PKCι, was investigated. PKCι is elevated in human and mouse pancreatic ADM and intraepithelial neoplastic lesions in vivo. We demonstrate that K-ras(G12D) is sufficient to induce pancreatic ADM in explant culture, exhibiting many of the same morphologic and biochemical alterations observed in TGF-α-induced ADM, including a dependence on Notch activation. PKCι is highly expressed in both TGF-α- and K-ras(G12D)-induced pancreatic ADM and inhibition of PKCι significantly reduces TGF-α- and K-ras(G12D)-mediated ADM. Inhibition of PKCι suppresses K-ras(G12D)-induced MMP-7 expression and Notch activation, and exogenous MMP-7 restores K-ras(G12D)-mediated ADM in PKCι-depleted cells, implicating a K-ras(G12D)-PKCι-MMP-7 signaling axis that likely induces ADM through Notch activation. Our results indicate that PKCι is an early marker of pancreatic neoplasia and suggest that PKCι is a potential downstream target of K-ras(G12D) in pancreatic ductal metaplasia in vivo.